Effects of Vegetated and Synthetic (Impervious) Surfaces on the Microclimate of Urban Area - MO Obiakor; CD Ezeonyejiaku; TC Mogbo (Journal of Applied Sciences and Environmental Management)
The present paper shows the considerable impacts of both vegetated and synthetic surfaces on the microclimate of urban area. Vegetation of a particular place affects the microclimate through reduced solar radiation and lower air temperature due to shading and evapotranspiration. Lower air temperatures are essential both to improve thermal comfort conditions of residents and to limit energy use for cooling. The growth and spread of synthetic (impervious) surfaces within urbanizing areas pose significant threats to the quality of natural and built environments. These threats include increased stormwater runoff, reduced water quality, higher maximum summer temperatures, degraded, and destroyed aquatic and terrestrial habitats, and the diminished aesthetic appeal of streams and landscapes. This paper provides a basic introduction to microclimate, vegetated and impervious surfaces and an overview of the effects of increased imperviousness and vegetation on the microclimate of urban areas. Although urban and suburban growth is inevitable, many of the environmental impacts of impervious surfaces are avoidable or controllable. Working together, local governments and citizens can reduce the amount of land rendered impervious, and can reduce its adverse impacts, promoting a healthier environment through sound landuse  planning and improved land management. @JASEM